The Social Condition of the 19th Century British Society Depicted in Jane Austen’s Mansfield Park Novel (International Journal of Scientific Research and Management (IJSRM), 2023)
This study delves into the nuanced portrayal of 19th-century British society within Jane Austen’s novel "Mansfield Park," employing Lucien Goldmann’s Genetic Structuralism as a theoretical lens. Through a meticulous examination of themes such as marriage as a financial transaction, educational disparities, social stratification, and implicit references to the institution of slavery, the research sheds light on the intricate layers of societal divisions and cultural norms prevalent in the Regency era. By analyzing textual excerpts and applying critical scrutiny, this article investigates the multifaceted dynamics of social classes, educational gaps, and the subtle yet significant portrayals of economic entanglements with the slave trade. In utilizing Goldmann’s theoretical framework, the study brings to the forefront the interplay between societal structures and cultural representations embedded within Austen’s literary work. Furthermore, this research seeks to unravel the complex web of interactions shaping the narrative, highlighting the interconnectedness of societal elements within "Mansfield Park." By elucidating the subtle nuances and underlying tensions in Austen’s portrayal of British society, the study aims to contribute to a deeper understanding of the socio-cultural fabric of the time. The exploration of Goldmann’s Genetic Structuralism as an analytical tool not only enriches the interpretation of Austen’s novel but also underscores the relevance of literary theory in unraveling the intricate layers of meaning inherent in classic literary works.